AIRCRAFT LAMINAR FLOW CONTROL1 - Joslin, Ronald D. (Annual Review of Fluid Mechanics, 1998)
▪ Abstract Aircraft laminar flow control (LFC) from the 1930s through the 1990s is reviewed and the current status of the technology is assessed. Examples are provided to demonstrate the benefits of LFC for subsonic and supersonic aircraft. Early studies related to the laminar boundary-layer flow physics, manufacturing tolerances for laminar flow, and insect-contamination avoidance are discussed. LFC concept studies in wind-tunnel and flight experiments are the major focus of the paper. LFC design tools are briefly outlined for completeness.
Keywords: manufacturing tolerance